Climate Change: An Inconvenient Maybe - Edwards, Gonzalo (Estudios de Economía, 2016)
The subject of Climate Change is here to stay for at least the rest of the 21st century. The extent to which climate change can be expected; the importance in its determination of anthropogenic factors, relative to natural causes; its impact on world agriculture, migration patterns and economic growth; the costs involved and the best practices to mitigate the consequences, are all still subject to great controversy and remain in the realm of the speculative, in spite of specific matters where a relative consensus has been reached, and despite media efforts to show only the more alarmist view. It is this controversy that gives the name to this essay, which advertently paraphrases former United States Vice-President Al Gore’s movie An Inconvenient Truth.